Multiple Lines of Evidence from Mitochondrial Genomes Resolve Phylogenetic Relationships of Parasitic Wasps in Braconidae. (8th August 2016) - Li, Qian; Wei, Shu-Jun; Tang, Pu; Wu, Qiong; Shi, Min; Sharkey, Michael J.; Chen, Xue-Xin
Abstract: The rapid increase in the number of mitochondrial genomes in public databases provides opportunities for insect phylogenetic studies; but it also provides challenges because of gene rearrangements and variable substitution rates among both lineages and sites. Typically, phylogenetic studies use mitochondrial sequence data but exclude other features of the mitochondrial genome from analyses. Here, we undertook large-scale sequencing of mitochondrial genomes from a worldwide collection of specimens belonging to Braconidae, one of the largest families of Metazoa. The strand-asymmetry of base composition in the mitochondrial genomes of braconids is reversed, providing evidence for monophyly of the Braconidae. We have reconstructed a backbone phylogeny of the major lineages of Braconidae from gene order of the mitochondrial genomes. Standard phylogenetic analyses of DNA sequences provided strong support for both Cyclostomes and Noncyclostomes. Four subfamily complexes, that is, helconoid, euphoroid, sigalphoid, and microgastroid, within the Noncyclostomes were reconstructed robustly, the first three of which formed a monophyletic group sister to the last one. Aphidiinae was recovered as a lineage sister to other groups of Cyclostomes, while the Ichneutinae was recovered as paraphyletic. Separate analyses of the subdivided groups showed congruent relationships, employing different matrices and methods, for the internal nodes of the Cyclostomes and the microgastroid complex of subfamilies. This research, using multiple lines of evidence from mitochondrial genomes, illustrates multiple uses of mitochondrial genomes for phylogenetic inference in Braconidae.